2005
DOI: 10.1002/chin.200537291
|View full text |Cite
|
Sign up to set email alerts
|

The Shape Memory Effect in Polymers

Abstract: Theoretical chemistry Z 0350 The Shape Memory Effect in Polymers -[205 refs.]. -(BELOSHENKO, V. A.; VARYUKHIN, V. N.; VOZNYAK, Y. V.; Russ. Chem. Rev. (Engl. Transl.) 74 (2005) 3, 265-283; Galkin Donetsk Physicotech. Inst., Natl. Acad. Sci. Ukr., Donetsk 340114, Ukraine; Eng.) -Lindner 37-291

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 1 publication
1
21
0
Order By: Relevance
“…Bending deformations can also be performed and the deflection visually monitored. Although tension to high strains ( 100%) [6,10,14,25,26,30,38,41] or bending at low strains are often analyzed [9,21,27,39], less effort has been focused on SM behavior in compression [15,16,19,20,22]. Compression strains of 11-150% have been reported [15,20].…”
Section: Shape Memory Properties: Definitions and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Bending deformations can also be performed and the deflection visually monitored. Although tension to high strains ( 100%) [6,10,14,25,26,30,38,41] or bending at low strains are often analyzed [9,21,27,39], less effort has been focused on SM behavior in compression [15,16,19,20,22]. Compression strains of 11-150% have been reported [15,20].…”
Section: Shape Memory Properties: Definitions and Characterizationmentioning
confidence: 99%
“…Shape Fixity, R f [6,9,14,16,17,25,26,30,38,39]. Shape fixity characterizes the ability of an SMP to fix the strain imparted in the sample during the deformation step after subsequent cooling and unloading.…”
Section: Shape Memory Properties: Definitions and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Reinforcement of SPU with different nanosized fillers like ferromagnetic nanoparticles, nanoceramics, metal nanopowders, nanoclays, carbon nanotubes (CNTs) for significant improvement in the mechanical and functional properties have been undertaken . However, CNTs are promising due to high aspect ratio, scope of surface modification and retention of aspect ratio during polymer processing . Both single wall CNTs and multiwall carbon nanotubes (MWCNTs) have been used to prepare polymer nanocomposites and it has been reported that ultimate performance of the nanocomposites depends on distribution and dispersion of the CNTs along with extent of crystallization .…”
Section: Introductionmentioning
confidence: 99%